1985
DOI: 10.3109/03009748509165503
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Studies of Complement Activation in Systemic Lupus Erythematosus

Abstract: C1 and C3 activation, measured as C1r-C1s-C1 inactivator C1s-C1r-C1IA complexes in serum and circulating C3d were studied in serial samples from 33 patients with SLE. All patients demonstrated exacerbations during observation periods of 10-30 months and were divided into groups according to principal clincal features (mild SLE, severe extra-renal SLE, and lupus glomerulonephritis). Increased C1 activation was consistently found during exacerbation. C3d in plasma was a feature associated with severe disease fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
6
30
1
Order By: Relevance
“…In contrast, Sturfelt et a1 (15) found that changes in levels of C4 and C3, and solid-phase Clq binding did not predict 8 renal and 16 nonrenal flares. Buyon et al (19) also found conventional measures of complement (C4, C3, and CH50) to be of limited value in predicting 8 renal and 14 nonrenal flares.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, Sturfelt et a1 (15) found that changes in levels of C4 and C3, and solid-phase Clq binding did not predict 8 renal and 16 nonrenal flares. Buyon et al (19) also found conventional measures of complement (C4, C3, and CH50) to be of limited value in predicting 8 renal and 14 nonrenal flares.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, tests for levels of complement split products, interleukin-2 receptor, and urinary free light chains, among other tests, have been reported to predict subsequent disease activity in recent studies (15)(16)(17)(18)(19). While they are of considerable interest for understanding the pathogenesis of SLE, these tests are not routinely available.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, C1q has many functions crucial for homeostasis and prevention of SLE. Accordingly, low serum levels of C1q correlates with severe active SLE (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although serum levels of C3, C4, and their activation-derived products are frequently used to monitor disease activity in SLE, their value as biomark-ers is a subject of controversy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These observations have led us to consider measurement of complement activation products bound to circulating blood cells (14,15).…”
mentioning
confidence: 99%